Pengaruh Penggunaan Media Timeline Tehadap Kemampuan Historical Thinking Siswa Kelas Xi Dalam Pembelajaran Sejarah Di SMKN 3 Pontianak - Putri, Putri; Chalimi, Ika Rahmatika; Putri, Astrini Eka (Jurnal Ilmiah Wahana Pendidikan, 2025)
The purpose of this research is to find out whether there is an influence of timeline media on students' historical thinking abilities. This research was carried out using quantitative methods and cluster random sampling techniques. Research data was obtained through observation, tests and documentation. Analysis of the research data obtained using the T Test (Independent T-Test) and Effect Size. Data collection techniques used by researchers are observation techniques, measurement techniques, document techniques. The data collection tools used by researchers are observation guidelines, tests and guidelines. The results of the research show (1) This research uses timeline media in history learning to get grades that tend to be low. (2) Based on the test results in the experimental class and control class through posttest-pretest questions, there were significant differences, namely in the experimental class, scores were 72.2 and 73.7. Meanwhile, in the control class, scores were 57.8 and 66.1. (3) Based on the calculation of the T Test (Independent T-Test) via SPSS, a significance level was obtained, namely 0.00 < 0.05 and a value of 0.83 was obtained through the effect size test in the large category. So it can be concluded that the use of timeline media on students' historical thinking abilities in learning history has an influence and has a big effect.